Estimating the Shelf Life of Yellow Pumpkin Instant Noodles Using the Arrhenius Model Approach in Different Packages : Pendugaan Umur Simpan Mi Instan Labu Kuning Menggunakan Pendekatan Model Arrhenius pada Kemasan yang Berbeda - Chapib Jamaludin; Iffah Muflihati; Arief Rakhman Affandi; Fafa Nurdyansyah (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Abstract Gluten-free pumpkin instant noodles is one of the developments of pumpkin-based processed products. The purpose of this study was to determine the shelf life of pumpkin instant noodles using the Arrhenius model ASLT method in different packaging. The types of packaging used were Polypropylene, Aluminium Foil, and SOS (Self-Opening Sack) Paper, which were stored for 42 days at 25, 35, and 45℃ with chemical and sensory variables taken every 7 days. The results of shelf life estimation follow the key parameters of free fatty acid content with the Arrhenius equation ln k =-347.08x-2.5626 and activation energy value of 689.301 cal/mol as the smallest activation value in all treatments. The estimated shelf life at 25℃, packed using SOS (Self-Opening Sack) paper packaging, has the longest shelf life of 67 days. Meanwhile, the aluminium foil and polypropylene packaging were 65 days and 60 days, respectively. As the length of storage increases, the shelf life of the product will get shorter. Abstrak Mi instan labu kuning bebas gluten merupakan salah satu pengembangan produk olahan berbasis labu kuning. Tujuan penelitian ini adalah untuk menentukan masa simpan mi instan labu kuning menggunakan metode ASLT model Arrhenius dalam kemasan berbeda. Jenis kemasan yang digunakan adalah Polypropylene, Alumunium Foil, dan Kertas SOS (Self Opening Sack) yang disimpan selama 42 hari pada suhu 25, 35, dan 45℃ dengan pengambilan variabel kimia dan sensori setiap 7 hari sekali. Hasil pendugaan umur simpan mengikuti parameter kunci kadar asam lemak bebas dengan persamaan Arrhenius ln k =-347,08x-2,5626 dan nilai Energi aktivasi 689,301 kal/mol sebagai nilai aktivasi terkecil pada semua perlakuan. Hasil pendugaan umur simpan pada suhu 25℃ yang dikemas menggunakan kemasan kertas SOS SOS (Self Opening Sack) memiliki umur simpan yang paling lama yaitu 67 hari. Sedangkan pada kemasan alumunium foil dan polypropilen berurutan adalah 65 hari dan 60 hari. Seiring bertambahnya lama penyimpanan umur simpan produk akan semakin pendek.